2016
DOI: 10.1126/science.aag0482
|View full text |Cite
|
Sign up to set email alerts
|

Mega-earthquakes rupture flat megathrusts

Abstract: The 2004 Sumatra-Andaman and 2011 Tohoku-Oki earthquakes highlighted gaps in our understanding of mega-earthquake rupture processes and the factors controlling their global distribution: A fast convergence rate and young buoyant lithosphere are not required to produce mega-earthquakes. We calculated the curvature along the major subduction zones of the world, showing that mega-earthquakes preferentially rupture flat (low-curvature) interfaces. A simplified analytic model demonstrates that heterogeneity in shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 46 publications
(4 reference statements)
5
92
3
Order By: Relevance
“…In addition, we found a positive correlation between the curvature of the incoming plate prior to subduction and swarm activity. Given that plate curvature is related to both the hydration of the incoming plate before subduction and heterogeneity on the plate interface [e.g., Ranero et al , ; Shillington et al , ; Bletery et al , ], the positive correlation between plate curvature and swarm activity implies that earthquake swarms are more likely to occur in subduction zones with abundant fluids and marked heterogeneity on the plate interface. SSEs are also known to occur in regions where fluids are abundant [ Kodaira et al , ; Saffer and Tobin , ], meaning that this correlation is also consistent with the idea that SSEs trigger earthquake swarms in subduction zones.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found a positive correlation between the curvature of the incoming plate prior to subduction and swarm activity. Given that plate curvature is related to both the hydration of the incoming plate before subduction and heterogeneity on the plate interface [e.g., Ranero et al , ; Shillington et al , ; Bletery et al , ], the positive correlation between plate curvature and swarm activity implies that earthquake swarms are more likely to occur in subduction zones with abundant fluids and marked heterogeneity on the plate interface. SSEs are also known to occur in regions where fluids are abundant [ Kodaira et al , ; Saffer and Tobin , ], meaning that this correlation is also consistent with the idea that SSEs trigger earthquake swarms in subduction zones.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that smoother megathrusts naturally lead to larger earthquakes because a more homogeneous interface allows for more uniform fault strength distributions (Bletery et al, 2016). Recent studies have suggested that smoother megathrusts naturally lead to larger earthquakes because a more homogeneous interface allows for more uniform fault strength distributions (Bletery et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Curvature of the megathrust is strongly correlated with average dip angle of the megathrust, but it is also influenced by dip of the deeper slab, which may cause shear strength to vary across the plate boundary. More shallowly dipping, flatter boundaries are able to support larger earthquakes due to more homogeneous strength (e.g., Bletery et al, 2016). The nature of the upper plate, being either continental or oceanic, also appears to be important, as are factors such as the presence of back-arc spreading and trench roll-back (Scholz and Campos, 2012).…”
Section: Large-scale Subduction Zone Parametersmentioning
confidence: 99%